Study of the consolidation and creep behavior of marl soil in the Rastain area - العبد الله, صفوان (Latakia University Journal -Engineering Sciences Series, 2024)
The marly soil in the Rastin-Latakia region is a sedimentary soil with a consistency between hard and semi-hard. It is spread in large thicknesses and in different colors in the sloping land of Rastin adjacent to the 6th Tishreen Dam. The settlement behavior of this soil is affected by the values of pre-stress, and its creep behavior on slopes is affected by the amount of its viscosity. index. The settlement values are related to the value of the Oedometric deformation modulus, taken in terms of stresses. In order to characterize the behavior of deformation, stress experiments were conducted on 19 samples taken from the boreholes in the studied area. The triaxial experiment was computer-modeled using the PLAXIS2020 program, and the values of n , w the constants of the Oedometer deformation modulus equation and the relationship between them and the moisture content and porosity were determined. Also, the values of the viscosity index Iv for the tested soil and its relationship to the liquid limit were determined to conclude the extent to which the results influence the assessment of the behavior of deformation and creep and the possibility of moving slopes in the area.